Two-dimensional metal phosphorus trisulfide nanosheet with solar hydrogen-evolving activity. (October 2017) - Wang, Fengmei; Shifa, Tofik Ahmed; He, Peng; Cheng, Zhongzhou; Chu, Junwei; Liu, Yang; Wang, Zhenxing; Wang, Feng; Wen, Yao; Liang, Lirong; He, Jun
Abstract: The development and utilization of photocatalysts to realize water-splitting without any external bias or sacrificial agents has received the limelight. As a novel two-dimensional layered material, metal phosphorus trichalcogenides (MPTs) cause wide research interest, presently. However, the growth of ultrathin two-dimensional MPT crystals is a great challenge to hinder their application. Here, we initially grow few-atomic layered nickel phosphorus trisulfide (NiPS3 ) as promising photocatalyst for hydrogen evolution. The as-prepared NiPS3 hexagonal nanosheet, as thin as few atomic layers (≤ 3.5 nm), has lateral size of larger than 15 µm. These ultrathin NiPS3 crystals can directly generate hydrogen gas from pure water without any sacrificial agents under sunlight. With ultraviolet photoelectron spectrometer and electrochemical impedance spectroscopy, we show that the attractive photocatalytic activity of the ultrathin NiPS3 crystals arise from their appropriate positions of the band edges. This discovery is expected to make a contribution to develop next generation solar-fuel conversion catalysts for H2 production. Graphical abstract: Large-scale ultrathin nickel phosphorus trisulfide (NiPS3 ) hexagonal nanosheets are successfully synthesized through chemical vapor deposition (CVD) method in this work. The lateral size of the NiPS3 nanosheet, as thin as 3.5 nm, is larger than 15 µm. Notably, these NiPS3 nanosheets demonstrate high crystal quality and intriguing solar-driven water splitting photocatalysis in pure water. Highlights: Large-scale ultrathin (≤ 3.5 nm)hexagonal NiPS3 nanosheets are successfully synthesized through chemical vapor deposition (CVD) method. The synthesized NiPS3 nanosheets can act as a novel photocatalyst to decompose water for H2 generation under solar light irradiation without any co-catalyst or sacrificial agents. The band structure of the 2D ultrathin NiPS3 was systematically studied via using ultraviolet photoelectron spectrometer and electrochemical impedance spectroscopy.